Inovasi “Labu Joy” dalam Pemberdayaan Ekonomi Masyarakat Melalui Diversifikasi Olahan Nugget Labu - Lenny Amelia HK Amelia; Bahmid I Magi; Rista Ade Liana Liana; Muhammad Ilyas Salim Salim (Ma'soem University, 2026)
Margaluyu Village is an area with high potential for chayote farming, with an agricultural land area of 470 hectares, accounting for approximately 54.638% of the total village area. However, farmers frequently face a severe issue of seasonal surplus, causing the selling price to plummet to Rp 2,500/kg. Furthermore, chayote spoils quickly after harvest, and the community lacks the skills to process the harvest into value-added products. This activity aims to optimize local potential through product diversification innovation in the form of chayote nuggets named